Evaluation of severity of chronic obstructive pulmonary disease using bronchial obstruction, dyspnea, exercise index and global initiative for chronic obstructive lung disease classification and it’s correlation with physical quality of life measured by St. George’s respiratory disease questionnaire score - Daga, Snehal; Khadke, Vrushali; Phalgune, Deepak; Chopadawala, Abbas (International Journal of Advances in Medicine, 2020)
Background: The Global initiative for chronic Obstructive Lung Disease (GOLD) criteria classified chronic obstructive pulmonary disease (COPD) by severity into four stages. Recently, Body mass index (BMI), Bronchial Obstruction, Dyspnea, Exercise (BODE) index, was proposed to provide useful prognostic information of COPD patients. Health-related quality of life (HRQOL) is measured by St. George’s Respiratory disease Questionnaire (SGRQ). Study was undertaken to assess correlations between BODE index and GOLD classification with SGRQ score. Methods: Fifty five COPD patients were included. Spirometry was performed in all patients. Modified Medical Research Council (mMRC) scale was used to label severity of dyspnea. Six-minute walking distance (6 MWD) was performed. BODE index was calculated by giving points to BMI, forced expiratory volume in one minute (FEV1), 6 MWD, and mMRC. SGRQ was used to determine HRQOL. Correlation analysis was done using Pearson’s method. Results: Mean symptoms, mean activity, mean impacts and mean total SGRQ score were significantly higher in patients having mMRC scale 0-1, patients who could walk ≤149 meters, and in patients who had GOLD III and IV class. Lesser the FEV1, higher the mMRC grade, and lesser the 6 MWD, worse was the quality of life. BODE index (r = 0.72) and GOLD classification (r =0.59) were significantly and positively correlated with symptoms score, activity score, impacts score and total SGRQ score. Conclusions: BODE index correlated better than the Gold classification with SGRQ score implying that apart from the airflow limitation, functional impairment measured by the 6MWT and mMRC also affect HRQOL.